Women’s Status in Contemporary Islamic Politics: Tafsir of Al Hurriyah, Al Musawah, Al Karamah and Al Adalah - Muhammad, Husein (Yayasan Jurnal Perempuan, 2014)
This paper examines theological sources of Islam on the status of women in Politics. Al Quran states that equality between men and women are guaranteed in politics such as in Quran: Ali Imran, 195; an Nahl, 97; at Taubah, 71. Islamic politics based on the following postulates: first, freedom (al Hurriyyah). Human beings are only serving God. Second, equality (Musawah, non-discriminatory). All human being are equal in front of Allah. Third, respect to other human beings (Karamah al Insan/ preserving the other human’s dignity). Fourth, justice (‘Adalah). Theological sources of Islam has given foundation for the contemporary status of women in politics which had long been stripped away due to misogynistic interpretation of Quran. Quran has ontologically supply equality and justice to human rights that can be used in politics and state affairs.